The Disease Associated Tau35 Fragment has an Increased Propensity to Aggregate Compared to Full-Length Tau - Lyu, Chen; Da Vela, Stefano; Al-Hilaly, Youssra; Marshall, Karen E.; Thorogate, Richard; Svergun, Dmitri; Serpell, Louise C.; Pastore, Annalisa; Hanger, Diane P. (Frontiers in Molecular Biosciences, 2021)
Tau35 is a truncated form of tau found in human brain in a subset of tauopathies. Tau35 expression in mice recapitulates key features of human disease, including progressive increase in tau phosphorylation, along with cognitive and motor dysfunction. The appearance of aggregated tau suggests that Tau35 may have structural properties distinct from those of other tau species that could account for its pathological role in disease. To address this hypothesis, we performed a structural characterization of monomeric and aggregated Tau35 and compared the results to those of two longer isoforms, 2N3R and 2N4R tau. We used small angle X-ray scattering to show that Tau35, 2N3R and 2N4R tau all behave as disordered monomeric species but Tau35 exhibits higher rigidity. In the presence of the poly-anion heparin, Tau35 increases thioflavin T fluorescence significantly faster and to a greater extent than full-length tau, demonstrating a higher propensity to aggregate. We used atomic force microscopy, transmission electron microscopy and X-ray fiber diffraction to demonstrate that Tau35 aggregates are morphologically similar to previously reported tau fibrils but they are more densely packed. These data increase our understanding of the aggregation inducing properties of clinically relevant tau fragments and their potentially damaging role in the pathogenesis of human tauopathies.